Essential Monet - Potts, Vanessa, 1971-; O'Mahony, Claire I. R.; Monet, Claude, 1840-1926. (Bath, UK : Parragon, 2000)
A collection of paintings by Claude Monet with historical context.
Keywords: Monet, Claude, -- 1840-1926 -- Criticism and interpretation; Painting, French -- 19th century; Painting, French -- 20th century; Impressionism (Art); Monet, Claude, -- 1840-1926.